Asesmen Temporal Degradasi Lamun di Pesisir Kepulauan Riau, Indonesia - Nur, Syarif; Nurdjaman, Susanna (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2025)
Seagrass plays a crucial role in coastal ecosystems, necessitating its preservation to maintain ecosystem health. This study addresses the degradation of seagrass meadows in the coastal regions of the Riau Islands, Indonesia, utilizing remote sensing techniques and spatial data analysis. Satellite imagery offers a cost-effective means of monitoring seagrass health in shallow coastal waters. In October 2020, the research team conducted the study at six stations—four on Lingga Island and two on Singkep Island. Utilized Sentinel-2 satellite imagery from 2019 and applied the Depth Invariant Index (DII) along with Support Vector Machine (SVM) classification. In-situ observations, conducted simultaneously, validated the satellite data and facilitated seagrass accuracy assessment, including species identification using the Seagrass-Watch (Transect Quadrant) methodology. The results reveal significant seagrass degradation in the Riau Islands. The DII method detected extensive seagrass losses, covering approximately 175 km2 of seagrass meadows across Lingga and Singkep Islands. Species identification confirmed the presence of Halophila ovalis, Halophila minor, Thalassia hemprichii, and identified Enhalus acoroides as the dominant species. This research gives important insights into the temporal degradation of seagrass environments along the coastal regions of the Riau Islands, highlighting the importance of continued monitoring and preservation efforts.